Packaging, Ingredient Branding, And Price As Determinants Of Consumer Brand Switching Intention: A Systematic Literature Review On Jhs Iodized Salt - Andi Alda Surkati; Ayuningtyas Yuli Hapsari (CV. AFDIFAL MAJU BERKAH, 2026)
Brand switching intention represents a critical retention challenge in the Fast-Moving Consumer Goods (FMCG) sector, particularly for commodity products characterized by high substitutability and minimal intrinsic differentiation. This study employs empirical evidence on the roles of packaging, ingredient branding, and price in shaping consumer brand switching intention, with contextual application to JHS Iodized Salt a domestic Indonesian salt brand facing competitive pressure from local and national competitors. Following screening of peer-reviewed publications from 2020 to 2025, twelve articles meeting rigorous inclusion criteria were selected for critical synthesis. Findings consistently demonstrate that packaging quality and informational content, alongside credible ingredient branding strategies, function as protective (negative) antecedents of switching intention by enhancing perceived functional quality, brand association, and consumer trust. Conversely, perceived price unfairness operates as the primary push factor that accelerates switching intention, particularly in traditional market ecosystems where price sensitivity is highest. Critically, the protective effects of packaging and ingredient branding are found to partially attenuate price-induced switching, suggesting a moderating interaction among variables. These findings generate three testable hypotheses and a conceptual framework for future empirical investigation in the Indonesian salt commodity market. Theoretical contributions to the Push-Pull-Mooring (PPM) model and brand switching literature are discussed, alongside practical implications for packaging strategy, nutritional branding, and competitive pricing policy.